Microbes in space: how bacteria could help sustain long-distance space travel - Dance, Amber (Nature (London), 2025)
So far, microorganisms have been research subjects or contaminants on space stations, but could they assist longer missions? So far, microorganisms have been research subjects or contaminants on space stations, but could they assist longer missions?